THE USE OF DIGITAL LITERACY IN HIGHER EDUCATION - Salim Salim; Asriyani Mulia Basri; Desy Liliani Husain; Afifah Nur Hidayah; Nurhayati Nurhayati (AL-ISHLAH: Jurnal Pendidikan, 2020)
The study aims to determine the use of digital literacy in the students of FKIP Universitas Halu Oleo. This type of research is quantitative research conducted in the Faculty of teacher training and education Universitas Halu Oleo Kendari in the academic period of the odd semester year 2019/2020. The results of this study indicated that in the dimension of access to digital literacy use in the students of FKIP Universitas Halu Oleo with a good category of 54.83%, in the dimension of digital literacy competency in the students of FKIP Universitas Halu Oleo has a good category of 40.11%, and there are differences in the use of digital literacy in the students FKIP Universitas Halu Oleo reviewed from its dimensional. Conclusion of this research is generally a portrait of the use of digital literacy in the students of FKIP Universitas Halu Oleo categorized quite well with the dimension of access strongly affect the ability of digital literacy students FKIP Universitas Halu Oleo